Immune response to SARS-CoV-2 vaccination in relation to peripheral immune cell profiles among patients with multiple sclerosis receiving ocrelizumab. Issue 9 (22nd February 2022) - Räuber, Saskia; Korsen, Melanie; Huntemann, Niklas; Rolfes, Leoni; Müntefering, Thomas; Dobelmann, Vera; Hermann, Alexander M; Kölsche, Tristan; von Wnuck Lipinski, Karin; Schroeter, Christina B; Nelke, Christopher; Regner-Nelke, Liesa; et al.
Abstract : Background: Vaccination has proven to be effective in preventing SARS-CoV-2 transmission and severe disease courses. However, immunocompromised patients have not been included in clinical trials and real-world clinical data point to an attenuated immune response to SARS-CoV-2 vaccines among patients with multiple sclerosis (MS) receiving immunomodulatory therapies. Methods: We performed a retrospective study including 59 ocrelizumab (OCR)-treated patients with MS who received SARS-CoV-2 vaccination. Anti-SARS-CoV-2-antibody titres, routine blood parameters and peripheral immune cell profiles were measured prior to the first (baseline) and at a median of 4 weeks after the second vaccine dose (follow-up). Moreover, the SARS-CoV-2-specific T cell response and peripheral B cell subsets were analysed at follow-up. Finally, vaccination-related adverse events were assessed. Results: After vaccination, we found anti-SARS-CoV-2(S) antibodies in 27.1% and a SARS-CoV-2-specific T cell response in 92.7% of MS cases. T cell-mediated interferon (IFN)-γ release was more pronounced in patients without anti-SARS-CoV-2(S) antibodies. Antibody titres positively correlated with peripheral B cell counts, time since last infusion and total IgM levels. They negatively correlated with the number of previous infusion cycles. Peripheral plasma cells were increased in antibody-positive patients. A positive correlation between T cell response and peripheral lymphocyte counts was observed. Moreover, IFN-γ release was negatively correlated with the time since the last infusion. Conclusion: In OCR-treated patients with MS, the humoral immune response to SARS-CoV-2 vaccination is attenuated while the T cell response is preserved. However, it is still unclear whether T or B cell-mediated immunity is required for effective clinical protection. Nonetheless, given the long-lasting clinical effects of OCR, monitoring of peripheral B cell counts could facilitate individualised treatment regimens and might be used to identify the optimal time to vaccinate.